COMPLETE GENOMIC ANALYSIS OF NEWCASTLE DISEASE VIRUS OF A RECENT PANZOOTIC ISOLATED FROM VACCINATED POULTRY FLOCK IN 2014 IN PAKISTAN - A. Wajid; M. Wasim; A. Batool; H. Sadia; T. Bibi; A. Basharat; S. Manzoor; T. Yaqub; M. Tayyab; S. F. Rehmani (Journal of Animal and Plant Sciences, 2017)
Newcastle disease (ND) is one of the most significant OIE listed disease that causes a huge economic losses in the poultry sector worldwide. ND is endemic in Pakistan and continues outbreaks have been reported in vaccinated and non-vaccinated birds. Sequence analysis revealed several amino acids substitutions at the functional domains of fusion (F) and hemagglutinin-neuroaminidase (HN) protein. The current study proposed that the vaccination is leading to pressure on the NDV to mutate into more virulent strains. We noticed that the host range of NDV is extending to pet and other species and suggest it could be due more virulent strains emerging. The NDV strain Chicken/NDV/Pak/AW-14 was isolated from the vaccinated chicken from a poultry farm located near Lahore, Punjab. The isolated was biologically and genetically characterized through intra cerebral pathogenicity index (ICPI) and real time PCR (rRT-PCR). To better understand the epidemiology of ND outbreak, the full genome was sequenced and phylogenetic analysis was performed on the basis of full F and genome sequencing. AW-14 isolate was categorized as a velogenicNDV strain assessed biologically by the ICPI (1.8) and polybasic amino acid residues at the F protein cleavage site. The complete genome was 15,192 nucleotides (nt) in length with six genes in order of 3՝-NP-P-M-F-HN-L-5՝. Several polymorphisms were identified at the functional domains of surface glycoprotein F and HN, including signal peptide, transmembrane domain, hepad repeat region and N-glycosylation site, transmembrane domain, neutralizing epitope respectively. Phylogenetic analysis showed that the AW-14 belongs to sub-genotype VIIi, the newly emerging NDV strain has been implicated in the recent outbreaks in Pakistan, Indonesia and Israel and becoming established in poultry sector through Asia and Middle East. Here, we provide a summary of the genetic evolution and molecular epidemiology of the vNDV strain suggesting responsible of a fifth panzootic.
Keywords: Newcastle disease; complete genome; vaccinated birds; phylogenetic analysis; Pakistan